The taxonomic position of the Neotropical genus Casandria Walker, 1857, with new synonymies and combinations (Lepidoptera: Erebidae, Catocalinae) - Vitor O. Becker (SHILAP, 2022)
Casandria Walker, 1857, is transferred from the Nolidae (Collomeninae) to the Erebidae (Catocalinae), as the senior synonym of Acathodica Schaus, 1894. Consequently, the species formerly associated with Acanthodica are herein transferred to Casandria: C. albiplena (L. B. Prout, 1919) (Acanthodica), comb. n., C. cabra (Dognin, 1894) (Acanthodica), comb. n., C. chiripa (Dognin, 1894) (Acanthodica), comb. n., C. coelebs (L. B. Prout, 1919) (Acanthodica), comb. n., C. drucei (Dognin, 1889) (Calocampa), comb. n., C. emittens Walker, 1857 [= Agrotis daunus Druce, 1894)], syn. n., [= Acanthodica grandis (Schaus, 1894)], syn. n., C. fassli (Zerny, 1916) (Acanthodica), comb. n., C. fosteri (Hampson, 1913) (Acanthodica), comb. n., C. frigida (Jones, 1921) (Acanthodica), comb. n., C. hages (Druce, 1900) (Acanthodica), comb. n., C. lignaris (Schaus, 1894) (Acanthodica), comb. n., C. penicillum (Felder & Rogenhofer, 1874 (Agrotis), comb. n., C. sinuilinea (L. B. Prout, 1919) (Acanthodica), comb. n., C. splendens (Druce, 1889) (Agrotis), comb. n., C. xylinoides (Schaus, 1894) (Acanthodica), comb. n. The following species, formerly associated to Casandria are herein transferred to Motya Walker, 1859: M. araea (Schaus, 1911) (Casandria), comb. n., M. flotsama (Dyar, 1914) (Casandria), comb. n., M. insignis (Dognin, 1914) (Casandria), comb. n., M. steniptera (Schaus, 1911) (Casandria), comb. n. A table of all taxa formerly associated with both Casandria and Acanthodica are presented in the “Nommenclature summary”, and illustrations of both the types of C. emittens Walker, 1857 and of A. grandis Schaus, 1894, as well of a live C. splendens (Druce, 1889), are also presented.